THE CORRELATION OF INDIVIDUAL FACTORS WITH ABSENTEEISM AMONG TEXTILE INDUSTRY WORKERS IN SURABAYA (PT X) DURING 2013 - Linggarwati, Yunita Putri; Nawawiwetu, Erwin Dyah (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: High absenteeism rate affect productivity.In turn, low productivity makes the company suffer loss. In Indonesia there are rarely researches on the issue although actually it needs much attention. Purpose: The aim of this research was to analyze the correlation between individual factors with absenteeism among workers of Ring Frame (Spinning I)PT. X in 2013. Method: This was an observational descriptives research with cross sectional approach of absenteeism during 2013. The population were workers who experienced absent in 2013 (43 peoples). The variables were individual factor (age,sex, workers status,married status,work span, and education level) and the absenteeism rate such as GAR (Gross Absence Rate),ASR (Absence Severity Rate), AFR (Absence Frequency Rate), Day lost, Spells and the control measures. Result: The results showedthat the days lost were 130 days/years, with frequency absenteeism of 85 spells. The absenteeism rate were : GAR 0,3 % ; ASR 1,1 days and AFR 0,65 spells.GAR, ASR, and AFR were in the normal limit, the highest rate of day lost in category < 3 days and the highest rate of spells in category 1-2 spells. The highest rate of case group found in : age group 25-35 years, women, persistent workers, married, has a work span of 5-14 years and the education level in senior high school. Conclusion: There were no significant correlation between individual factors and absenteeism.